Sebuah Kesalahan Analisis Pada Subtitle English - Indonesia Di Film The Way, Way Back - Aldinata, Dyansyah; Hilman, Evert Haryanto (Universitas Putera Batam, 2022)
This research aims to find the error analysis that can be found in The Way, Way Back (2013) movie. The source data was taken from English to Indonesian subtitles. Based on Carl James theory (2008) there are substance error, text error, grammar error and lexical error. There are also two causes of errors: interlingual and intralingual. This research used a descriptive qualitative method. Error analysis occurs because lack of vocabulary, words, and structure. To finished this study, the researcher watched the movie, gather the data and pick which word that had error analysis. Based on the data analysis there were lexical errors and text error that found in 100 data, which consist 44 lexical errors (44%) 56 text errors (56%) 3 grammar errors (3%) and 1 substance errors (1%). The cause of error, 64 interlingual (64%) and 36 intralingual (36%)